From Bin Laden to Facebook 10 days of abduction, 10 years of terrorism - Ressa, Maria (World Scientific Publishing Co. Pte.Ltd., 2013)
Maria A Ressa has been interviewed by The Wall Street Journal ( High-Profile Journalist Reshapes Her Role in Terrorism Fight )The two most wanted terrorists in Southeast Asia - a Malaysian and a Singaporean - are on the run in the Philippines, but they manage to keep their friends and family updated on Facebook. Filipinos connect with al-Qaeda-linked groups in Somalia and Yemen. The black flag - embedded in al-Qaeda lore - pops up on websites and Facebook pages from around the world, including the Philippines, Indonesia, the Middle East, Afghanistan, Australia, and North Africa